Psychometric properties of the nursing start-up attitude scale in Iranian nursing students - Iman Jafari; Mehdi Jafari-Oori; Abbas Ebadi (BMC Nursing)
Abstract Background Entrepreneurial attitudes among nursing students are crucial for fostering innovation and addressing the evolving challenges in healthcare. However, measuring these attitudes accurately requires robust and validated instruments. The Nursing Start-up Attitude Scale is a valid and reliable instrument specifically designed to measure nursing students' attitudes towards start-ups. However, its psychometric properties in the context of the Iranian nursing field have not been thoroughly examined. Methods This methodological study was conducted online between 2021 and 2023, involving nursing students from various universities across Iran. The study employed the following procedures: forward–backward translation, assessment of face and content validities, concurrent validity analysis (n = 80 nursing students), exploratory factor analysis (n = 120), confirmatory factor analysis (n = 220), and reliability analysis, which included the assessment of Cronbach's alpha coefficient, interclass correlation coefficient, interpretability, and ceiling and floor effects. Results A total of 370 nursing students participated in the study. After ensuring the face and content validities, the concurrent validity was confirmed (r = 0.89). The five factors extracted in the exploratory factor analysis, which accounted for 80.74% of the explained variance, were subsequently confirmed in the confirmatory factor analysis. The Cronbach's alpha coefficient was found to be 0.85. Additionally, the interclass correlation coefficient for the total scale was 0.812, and there were no ceiling or floor effects observed (0%). Conclusion The present study confirms the validity and reliability of the Nursing Start-up Attitude Scale in the Iranian context. This scale can serve as a valuable tool for identifying both the strengths and areas for improvement in nursing entrepreneurial education programs. By utilizing the Nursing Start-up Attitude Scale, these programs can effectively enhance the development of entrepreneurial skills among future nursing professionals.